2015
DOI: 10.1371/journal.pone.0116136
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Like Rhythm in a Voiced and Voiceless Orangutan Call

Abstract: The evolutionary origins of speech remain obscure. Recently, it was proposed that speech derived from monkey facial signals which exhibit a speech-like rhythm of ∼5 open-close lip cycles per second. In monkeys, these signals may also be vocalized, offering a plausible evolutionary stepping stone towards speech. Three essential predictions remain, however, to be tested to assess this hypothesis' validity; (i) Great apes, our closest relatives, should likewise produce 5Hz-rhythm signals, (ii) speech-like rhythm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…Focusing on individual vocal rhythms, early descriptive work remarked temporal regularities in gelada monkeys’ vocalizations, a claim which is intriguing but purely descriptive, unfortunately not supported by quantitative data or statistical inference. More recent work in macaques and orangutans noted a 5‐Hz isochronous pattern during lip‐smacking, facial movement, or vocalization . Primate perspectives on speech rhythm can be found elsewhere (e.g., see Ref.…”
Section: Human and Nonhuman Studies Of Vocal Rhythmmentioning
confidence: 95%
See 1 more Smart Citation
“…Focusing on individual vocal rhythms, early descriptive work remarked temporal regularities in gelada monkeys’ vocalizations, a claim which is intriguing but purely descriptive, unfortunately not supported by quantitative data or statistical inference. More recent work in macaques and orangutans noted a 5‐Hz isochronous pattern during lip‐smacking, facial movement, or vocalization . Primate perspectives on speech rhythm can be found elsewhere (e.g., see Ref.…”
Section: Human and Nonhuman Studies Of Vocal Rhythmmentioning
confidence: 95%
“…More recent work in macaques and orangutans noted a 5-Hz isochronous pattern during lip-smacking, facial movement, or vocalization. [35][36][37] Primate perspectives on speech rhythm can be found elsewhere (e.g., see Ref. 21), but it is clear that we do need to understand more about vocal rhythms in our closest living relatives, the primates.…”
Section: Spontaneous Individual Vocal Rhythms: What Kind Of Temporal mentioning
confidence: 99%
“…In one study, macaque monkeys were even observed to spontaneously modify the vocal properties of their contact call for requesting different objects from the experimenter ( Hihara et al , 2003). Anecdotal reports of more generalized volitional vocal control, albeit rudimentary, in apes ( Hayes & Hayes, 1952; Hopkins et al , 2007; Kalan et al , 2015; Koda et al , 2007; Koda et al , 2012; Lameira et al , 2015; Laporte & Zuberbühler, 2010; Perlman & Clark, 2015; Taglialatela et al , 2003; Wich et al , 2008) suggest that the direct connections between the IFG and the brainstem motor nuclei were strengthened prior to our divergence from our apian relatives.…”
Section: Introductionmentioning
confidence: 83%
“…Other primates' vocal tracts are capable of producing a human-like range of vowels Boë et al, 2017) and consonants (Lameira et al, 2015(Lameira et al, , 2016(Lameira et al, , 2017. The overall conclusion is that the complexity of human speech, including its rhythmical nuances, must have neural, rather than morphological, bases (Ravignani et al, 2014b;Fitch et al, 2016;Belyk and Brown, 2017).…”
Section: Speech Rhythm and Comparative Anatomy Of Vocal Tractsmentioning
confidence: 99%